Benefit of surgical resection of distant metastasis in soft tissue sarcoma: a systematic review. (6th April 2021) - Hayashi, Katsuhiro; Hiraoka, Koji; Akiyama, Toru; Iwata, Shintaro; Tsuchiya, Hiroyuki; Kawai, Akira
Abstract: Objective: The aim of this systematic review was to evaluate the efficacy of metastasectomy for patients with advanced soft tissue sarcoma and to develop a recommendation outlining clinical guidelines for soft tissue sarcoma. Methods: We searched the pertinent literature from January 1985 to December 2017. Two reviewers evaluated and screened the literature independently for eligibility and extracted data. We evaluated the quality of body of evidence and made a recommendation according to the Grading of Recommendations Development and Evaluation methodology. Results: Among 244 identified studies, only 10 were finally included in this review and no randomized controlled trial reports were present. The median survival period after metastasectomy ranged from 9.6 to 39.6 months, and the 5-year survival rate ranged from 8 to 52%. The complication rate ranged from 7.3 to 25%, and the perioperative mortality rate was 0–1%. The guidelines committee proposed 'Metastasectomy can be offered for malignant soft tissue tumours with distant metastases'. This recommendation gained 100% consensus among the members of the guidelines group. Conclusions: Although the level of evidence is very low, many retrospective studies support a clinical advantage for metastasectomy, and surgical indications should be carefully considered for patients with metastasis from soft tissue sarcoma. Metastasectomy is an option for patients with metastasis and should be done only if it can be performed safely and if potential advantages outweigh disadvantages. Abstract : Many retrospective studies support a clinical advantage for metastasectomy, and surgical indications should be carefully considered for patients with metastasis from soft tissue sarcoma.